Association of BoLA-DRB3.2 alleles with fusobacteriosis in cows - T. M. Suprovych; M. P. Suprovych; R. V. Kolinchuk; T. M. Karchevska; I. O. Chornyi; V. A. Kolodiy (Regulatory Mechanisms in Biosystems, 2020)
The Major Histocompatability Complex (MHC) determines the immune response to pathogens, and its genes are promising candidates for the search of associations with diseases. A special role is played by BoLA-DRB3 gene, the product of which directly participates in the binding of alien antigens and conditions the specificity of the immune response. The second exon of this gene codes β1-domain of class II antigens, which is necessary for binding a broad spectrum of alien antigens. Exon 2 of BoLA-DRB3 gene is extremely polymorphic, giving the possibility to search the associations of its alleles with various diseases. The article provides the results of the study on polymorphism of alleles of BoLA-DRB3.2 gene for detection of its associations with sensitivity to fusobacteriosis (necrobacteriosis) of cows. The survey was performed using PCR-RFLP method with DNA of blood from 176 cows of two herds of Ukrainian black-and-white dairy breed. As a result of the studies, in the first herd, 25 BoLA-DRB3.2 alleles were found. In the selections of nectobacteriosis susceptible and resistant cows, we found 22 and 21 variants respectively. In the second herd, in the general selection and group of healthy animals, 27 alleles were typed, and 22 in the group of susceptible cows. BoLA-DRB3.2*22 allele was the commonest in both herds in both general selections and groups of nectobacteriosis-resistant cows. In the selection of susceptible animals, the commonest was the variant BoLA-DRB3.2*16. We determined statistically significant associations of BoLA-DRB3.2 alleles with sensitivity to nectobacteriosis of cattle. BoLA-DRB3.2*03 and *22 alleles associate with nectobacteriosis-resistant, while *16 and *23 – with nectobacteriosis-susceptible cows of the both studied groups. Also, in the first herd, another allele was found – *24, indicating close relationship with the disease. The studies of polymorphism of BoLA-DRB3 gene expand the knowledge about genetic peculiarities of the Ukrainian black-and-white dairy breed. The identified molecular-genetic markers could be useful for breeders whose work is oriented towards the formation of herds which are resistant to diseases of the limbs in cattle.